2021
DOI: 10.1016/j.bbrep.2021.100961
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol promotes stress tolerance via DAF-16 in Caenorhabditis elegans

Abstract: In this study, we studied the effects of cortisol and cortisone on the age-related decrease in locomotion in the nematode Caenorhabditis elegans and on the tolerance to heat stress at 35 °C and to oxidative stress induced by the exposure to 0.1% H 2 O 2 . Changes in mRNA expression levels of C. elegans genes related to stress tolerance were also analyzed. Cortisol treatment restored nematode movement following heat stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…In N2 worms, nuclear DAF-16 accumulates in older but not in young animals [ 24 ]. The accumulation of DAF-16 is accelerated earlier under external stress conditions such as high temperature and oxidative stress [ 42 ]. This suggests that the activation of DAF-16 might be driven by aging.…”
Section: Discussionmentioning
confidence: 99%
“…In N2 worms, nuclear DAF-16 accumulates in older but not in young animals [ 24 ]. The accumulation of DAF-16 is accelerated earlier under external stress conditions such as high temperature and oxidative stress [ 42 ]. This suggests that the activation of DAF-16 might be driven by aging.…”
Section: Discussionmentioning
confidence: 99%
“…Paratyphi A could significantly increase the nuclear localization of DAF-16 ( Figure 4C ; Supplementary Figure 2 ). We also analyzed the expression of daf-16 and its downstream target genes sod-3 , hsp-12.6 and dod-19 ( 44 ). The results indicated that S .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the results from transgenic strain TJ356 zIs356 [daf-16p::daf-16a/b:: GFP +rol-6(su1006)] indicated that S. Paratyphi A could significantly increase the nuclear localization of DAF-16 (Figure 4C; Supplementary Figure 2). We also analyzed the expression of daf-16 and its downstream target genes sod-3, hsp-12.6 and dod-19 (44). The results indicated that S. Paratyphi A significantly upregulated the expression of sod-3, hsp-12.6 and dod-19 (Figure 4D; Supplementary Table 12).…”
Section: Defense Against S Paratyphi a May Require The Participation ...mentioning
confidence: 91%
“…After 3 days of treatment, nematodes were transferred onto the fresh NGM plates (80 worms on each plate) and incubated at 35 °C for 10 h [ 48 ]. Numbers of survival nematodes were counted after the heat shock and the survival rate was calculated.…”
Section: Methodsmentioning
confidence: 99%